2014
DOI: 10.1073/pnas.1412631111
|View full text |Cite
|
Sign up to set email alerts
|

Modeling host interactions with hepatitis B virus using primary and induced pluripotent stem cell-derived hepatocellular systems

Abstract: Hepatitis B virus (HBV) chronically infects 400 million people worldwide and is a leading driver of end-stage liver disease and liver cancer. Research into the biology and treatment of HBV requires an in vitro cell-culture system that supports the infection of human hepatocytes, and accurately recapitulates virus-host interactions. Here, we report that micropatterned cocultures of primary human hepatocytes with stromal cells (MPCCs) reliably support productive HBV infection, and infection can be enhanced by bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
259
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(269 citation statements)
references
References 36 publications
8
259
2
Order By: Relevance
“…The development of new in vitro methods of HBV infection will soon shed some light on the recognition of HBV by PRRs. [98][99][100] Previous studies indicated that HBV infection apparently does not activate innate immunity in chimpanzees and patients. HBV proteins, such as HBsAg, HBx and HBV polymerase, are associated with the inhibition of TLR or RLR signaling pathways and lead to impaired IFN production.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new in vitro methods of HBV infection will soon shed some light on the recognition of HBV by PRRs. [98][99][100] Previous studies indicated that HBV infection apparently does not activate innate immunity in chimpanzees and patients. HBV proteins, such as HBsAg, HBx and HBV polymerase, are associated with the inhibition of TLR or RLR signaling pathways and lead to impaired IFN production.…”
Section: Discussionmentioning
confidence: 99%
“…Using experimentally infected chimpanzees, microarray analyses suggested that HBV, early in infection, does not modulate host cellular gene transcription significantly and would induce neither innate antiviral responses in hepatocytes nor intrahepatic innate immune responses (7). After this study, HBV was designated as a "stealth virus" (8), but this may not be the case (9). Furthermore, a study demonstrated that HBV may be cleared from infected hepatocytes before any detectable adaptive immune response (10), thus suggesting that innate immunity or antiviral responses at the level of infected cells could play an important role.…”
mentioning
confidence: 99%
“…146,147 Studies on MPCC with hiPSC-derived human hepatocytes 148 indicate a similar sensitivity toward drug toxicity as observed in MPCC using PHH. 51 In addition, hepatocytes generated from pluripotent stem cells have been successfully applied in in vitro studies on infectious diseases like hepatitis B and C infection 149,150 or malaria pathogenesis. 151 Moreover, inherited metabolic liver diseases can be modeled by reprogramming cells from those patients and differentiating hiPSC into the affected cell type, as shown for a1-antitrypsin deficiency, familial hypercholesterolemia, and glycogen storage disease type 1a.…”
mentioning
confidence: 99%